Effects of Prolonged Use of Mixed Reality Systems in Occupational Settings Discussion Panel. (September 2018) - Garrett, Gregory A.; Reid, Christopher R.; Jenkins, Michael; Talbot, Thomas; Doherty, Shawn
Augmented or mixed reality devices overlay computer-generated sensory information that alters one's current view of the real world. Gaming, military, and instructional applications are fairly prevalent, however, industrial applications are still in their infancy despite this dramatic increase in commercial products. Being a novel application to industry, designers of these systems have focused on function; but have only given a cursory look towards user population safety, ergonomic risk hazards, and long-term exposure concerns. How should designers design for human safety use concerns while maintaining system function? Besides form and function what, if any, safety considerations should public consumers and industries contemplate before buying commercial ready off-the-shelf systems? Ultimately, how do we use ergonomics assessments to better design, assess, and demonstrate business case use of mixed reality devices to benefit labor-intensive occupational tasks? The session will start with initial lectures and introductions from the panel, followed by an encouraged panel discussion with the audience led by the moderators. Moderators: Gregory Garrett, chair & Christopher Reid, co-chair